Persepsi Pelaku UMKM terhadap Penggunaan QRIS sebagai Metode Pembayaran Digital di Kabupaten Sumbawa: Pendekatan Kualitatif - Nisa, Baiq Hidayatun; Raudhatul Ilmi; Saindra; Feri Irawan (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This study aims to describe the perceptions of MSME players in Sumbawa Regency towards the use of QRIS (Quick Response Indonesian Standard) as a digital payment method. Using a qualitative approach and a literature study of various related studies, this paper explores the factors that influence the acceptance of QRIS payment technology in MSME players as well as the benefits and challenges faced in its implementation. The results show that MSME players generally view QRIS as a practical, safe payment solution that can help increase turnover, although there are still obstacles such as limited understanding of technology and unstable internet networks. This study recommends increasing socialization and training as well as strengthening digital infrastructure to encourage wider adoption of QRIS in Sumbawa Regency.